At the heart of morality lies neuro-visceral integration: lower cardiac vagal tone predicts utilitarian moral judgment - Park, G; Kappes, A; Rho, Y; Van Bavel, J (Oxford University Press, 2016)
To not harm others is widely considered the most basic element of human morality. The aversion to harm others can be either rooted in the outcomes of an action (utilitarianism) or reactions to the action itself (deontology). We speculated that the human moral judgments rely on the integration of neural computations of harm and visceral reactions. The present research examined whether utilitarian or deontological aspects of moral judgment are associated with cardiac vagal tone, a physiological proxy for neuro-visceral integration. We investigated the relationship between cardiac vagal tone and moral judgment by using a mix of moral dilemmas, mathematical modeling and psychophysiological measures. An index of bipolar deontology-utilitarianism was correlated with resting heart rate variability (HRV)-an index of cardiac vagal tone-such that more utilitarian judgments were associated with lower HRV. Follow-up analyses using process dissociation, which independently quantifies utilitarian and deontological moral inclinations, provided further evidence that utilitarian (but not deontological) judgments were associated with lower HRV. Our results suggest that the functional integration of neural and visceral systems during moral judgments can restrict outcome-based, utilitarian moral preferences. Implications for theories of moral judgment are discussed.